Regional Economic Transformation Through The Establishment of A New Industrial Growth Center In Riau Islands Province In 2020 - Prameswari, Evany Sofia; Ganjar Winasis; Muhammad Syahrian Zulkarnain; Alvito Abimanyu (Universitas Negeri Semarang, 2025)
The Kepulauan Riau Province, despite its significant industrial potential, faces economic disparity between regions due to its archipelagic geography. This study aims to identify strategies for establishing new industrial growth centers that can attract investment and reduce regional disparities. The approach employed includes the analysis of Gross Regional Domestic Product (GRDP) and the application of several analytical methods, namely Shift-Share, Location Quotient (LQ), and Multiplier Effect. The results of the analysis indicate that establishing an industrial growth center in Natuna Regency, which possesses abundant natural resources, particularly in the fisheries and energy sectors, is a strategic step to stimulate economic growth and reduce regional disparities. The selection of this growth center location also aligns with the principles outlined by François Perroux regarding the characteristics of growth poles